2024
DOI: 10.3390/ijms25031628
|View full text |Cite
|
Sign up to set email alerts
|

Onco-Breastomics: An Eco-Evo-Devo Holistic Approach

Anca-Narcisa Neagu,
Danielle Whitham,
Pathea Bruno
et al.

Abstract: Known as a diverse collection of neoplastic diseases, breast cancer (BC) can be hyperbolically characterized as a dynamic pseudo-organ, a living organism able to build a complex, open, hierarchically organized, self-sustainable, and self-renewable tumor system, a population, a species, a local community, a biocenosis, or an evolving dynamical ecosystem (i.e., immune or metabolic ecosystem) that emphasizes both developmental continuity and spatio-temporal change. Moreover, a cancer cell community, also known as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 323 publications
0
5
0
Order By: Relevance
“…We used NGS-based targeted resequencing and Sanger sequencing for clinical validation of ZNF G64A mutation as AP-/BC-CML. Targeted resequencing and Sanger sequencing along with other similar techniques are routinely being used for clinical validation of molecular biomarkers [38-45]. Moreover, incorporation of next-generation sequencing, and other high-throughput techniques have refined the discovery and validation of diagnostic and prognostic biomarkers and their incorporation into precision medicine [43-51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used NGS-based targeted resequencing and Sanger sequencing for clinical validation of ZNF G64A mutation as AP-/BC-CML. Targeted resequencing and Sanger sequencing along with other similar techniques are routinely being used for clinical validation of molecular biomarkers [38-45]. Moreover, incorporation of next-generation sequencing, and other high-throughput techniques have refined the discovery and validation of diagnostic and prognostic biomarkers and their incorporation into precision medicine [43-51].…”
Section: Discussionmentioning
confidence: 99%
“…We used NGS-based targeted resequencing and Sanger sequencing for clinical validation of ZNF G64A mutation as AP-/BC-CML. Targeted resequencing and Sanger sequencing along with other similar techniques are routinely being used for clinical validation of molecular biomarkers [38][39][40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BC is commonly described as an ecological and environmental sickness or disorder [161][162][163]. To sustain this hypothesis, numerous studies have indicated that certain environmental exposures and lifestyle variables contribute 70% to 95% of the different risk factors that influence the incidence of breast cancer [164].…”
Section: Ecological Factors That Cause Bc Disparitiesmentioning
confidence: 99%
“…The aim of this review is to deepen our understanding of the study of breast cancer as an ”environmental disease”, using an exposomics-based hypothesis sustaining that BC is an “ecological disorder” [ 1 , 2 , 3 ]. We are what we eat [ 4 , 5 , 6 , 7 , 8 ], we are what we breathe [ 9 ], and we are what we live in [ 10 ].…”
Section: Introductionmentioning
confidence: 99%

Breast Cancer Exposomics

Neagu,
Jayaweera,
Corrice
et al. 2024
Life
Self Cite